2014
DOI: 10.1007/s11262-014-1035-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel finding for enterovirus virulence from the capsid protein VP1 of EV71 circulating in mainland China

Abstract: Enterovirus 71 (EV71) is a neurotropic virus that causes various clinical manifestations in young children, ranging from asymptomatic to fatal. Different pathotypes of EV71 notably differ in virulence. Several virulence determinants of EV71 have been predicted. However, these reported virulence determinants could not be used to identify the EV71 strains of subgenotype C4, which mainly circulate in China. In this study, VP1 sequences of 37 EV71 strains from severe cases (SC-EV71) and 192 EV71 strains from mild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…The vertex of the 5-fold axis of EV71 plays an important role in not only viral entry but also viral pathogenicity. Molecular epidemiological studies have suggested that VP1-98K and VP1-145G/Q isolates are more frequently detected in cases with severe neurological disease in humans than are VP1-98E and VP1-145E isolates, respectively (41,42). However, on the other hand, substitution of VP1-145G/Q for VP1-145E was found to be responsible for adaptation and/or virulence in both murine and primate models, either alone or in combination with other amino acids (43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…The vertex of the 5-fold axis of EV71 plays an important role in not only viral entry but also viral pathogenicity. Molecular epidemiological studies have suggested that VP1-98K and VP1-145G/Q isolates are more frequently detected in cases with severe neurological disease in humans than are VP1-98E and VP1-145E isolates, respectively (41,42). However, on the other hand, substitution of VP1-145G/Q for VP1-145E was found to be responsible for adaptation and/or virulence in both murine and primate models, either alone or in combination with other amino acids (43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the viral factors associated with severe clinical outcome remain unclarified. To date, some groups have argued that the amino acid substitutions in capsid protein VP1 of EV‐A71 strains might contribute to the different severity of the disease [Liu et al, ]. However, the mechanism for the severity caused by EV‐A71 is quite complex [Lin et al, ; Zhang et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that non-PB strains are mainly responsible for the development of viremia and neuropathogenesis. In humans, VP1-145G or VP1-145Q was isolated more frequently from severely affected patients than from mildly affected patients, although the majority of viruses isolated from both patient types have E at position 145 (24)(25)(26)(27). In the accompanying paper (28), we showed that VP1-145E is more virulent than VP1-145G in an hSCARB2 transgenic (tg) mouse model.…”
mentioning
confidence: 89%